Answer:
4. The equation of the perpendicular bisector is y =
x -
5. The equation of the perpendicular bisector is y = - 2x + 16
6. The equation of the perpendicular bisector is y =
x +
Step-by-step explanation:
Lets revise some important rules
- The product of the slopes of the perpendicular lines is -1, that means if the slope of one of them is m, then the slope of the other is
(reciprocal m and change its sign) - The perpendicular bisector of a line means another line perpendicular to it and intersect it in its mid-point
- The formula of the slope of a line is
- The mid point of a segment whose end points are
and
is
- The slope-intercept form of the linear equation is y = m x + b, where m is the slope and b is the y-intercept
4.
∵ The line passes through (7 , 2) and (4 , 6)
- Use the formula of the slope to find its slope
∵
= 7 and
= 4
∵
= 2 and
= 6
∴ ![m=\frac{6-2}{4-7}=\frac{4}{-3}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7B6-2%7D%7B4-7%7D%3D%5Cfrac%7B4%7D%7B-3%7D)
- Reciprocal it and change its sign to find the slope of the ⊥ line
∴ The slope of the perpendicular line =
- Use the rule of the mid-point to find the mid-point of the line
∴ The mid-point = ![(\frac{7+4}{2},\frac{2+6}{2})](https://tex.z-dn.net/?f=%28%5Cfrac%7B7%2B4%7D%7B2%7D%2C%5Cfrac%7B2%2B6%7D%7B2%7D%29)
∴ The mid-point = ![(\frac{11}{2},\frac{8}{2})=(\frac{11}{2},4)](https://tex.z-dn.net/?f=%28%5Cfrac%7B11%7D%7B2%7D%2C%5Cfrac%7B8%7D%7B2%7D%29%3D%28%5Cfrac%7B11%7D%7B2%7D%2C4%29)
- Substitute the value of the slope in the form of the equation
∵ y =
x + b
- To find b substitute x and y in the equation by the coordinates
of the mid-point
∵ 4 =
×
+ b
∴ 4 =
+ b
- Subtract
from both sides
∴
= b
∴ y =
x -
∴ The equation of the perpendicular bisector is y =
x -
5.
∵ The line passes through (8 , 5) and (4 , 3)
- Use the formula of the slope to find its slope
∵
= 8 and
= 4
∵
= 5 and
= 3
∴ ![m=\frac{3-5}{4-8}=\frac{-2}{-4}=\frac{1}{2}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7B3-5%7D%7B4-8%7D%3D%5Cfrac%7B-2%7D%7B-4%7D%3D%5Cfrac%7B1%7D%7B2%7D)
- Reciprocal it and change its sign to find the slope of the ⊥ line
∴ The slope of the perpendicular line = -2
- Use the rule of the mid-point to find the mid-point of the line
∴ The mid-point = ![(\frac{8+4}{2},\frac{5+3}{2})](https://tex.z-dn.net/?f=%28%5Cfrac%7B8%2B4%7D%7B2%7D%2C%5Cfrac%7B5%2B3%7D%7B2%7D%29)
∴ The mid-point = ![(\frac{12}{2},\frac{8}{2})](https://tex.z-dn.net/?f=%28%5Cfrac%7B12%7D%7B2%7D%2C%5Cfrac%7B8%7D%7B2%7D%29)
∴ The mid-point = (6 , 4)
- Substitute the value of the slope in the form of the equation
∵ y = - 2x + b
- To find b substitute x and y in the equation by the coordinates
of the mid-point
∵ 4 = -2 × 6 + b
∴ 4 = -12 + b
- Add 12 to both sides
∴ 16 = b
∴ y = - 2x + 16
∴ The equation of the perpendicular bisector is y = - 2x + 16
6.
∵ The line passes through (6 , 1) and (0 , -3)
- Use the formula of the slope to find its slope
∵
= 6 and
= 0
∵
= 1 and
= -3
∴ ![m=\frac{-3-1}{0-6}=\frac{-4}{-6}=\frac{2}{3}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7B-3-1%7D%7B0-6%7D%3D%5Cfrac%7B-4%7D%7B-6%7D%3D%5Cfrac%7B2%7D%7B3%7D)
- Reciprocal it and change its sign to find the slope of the ⊥ line
∴ The slope of the perpendicular line = ![-\frac{3}{2}](https://tex.z-dn.net/?f=-%5Cfrac%7B3%7D%7B2%7D)
- Use the rule of the mid-point to find the mid-point of the line
∴ The mid-point = ![(\frac{6+0}{2},\frac{1+-3}{2})](https://tex.z-dn.net/?f=%28%5Cfrac%7B6%2B0%7D%7B2%7D%2C%5Cfrac%7B1%2B-3%7D%7B2%7D%29)
∴ The mid-point = ![(\frac{6}{2},\frac{-2}{2})](https://tex.z-dn.net/?f=%28%5Cfrac%7B6%7D%7B2%7D%2C%5Cfrac%7B-2%7D%7B2%7D%29)
∴ The mid-point = (3 , -1)
- Substitute the value of the slope in the form of the equation
∵ y =
x + b
- To find b substitute x and y in the equation by the coordinates
of the mid-point
∵ -1 =
× 3 + b
∴ -1 =
+ b
- Add
to both sides
∴
= b
∴ y =
x +
∴ The equation of the perpendicular bisector is y =
x +